SnO2-CdO ceramic gas sensor - 288596 Mazlina Mat Darus; Md. Rahim Sahar, 1957-; Mohd. Mustamam Abd. Karim; Persidangan Serantau Sains Keadaan Pepejal (ke-16 : 1999 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 1999)
50